Outcomes of Drug-Coated Balloon (DCB) Angioplasty in Small Vessel Coronary Artery Disease - Saeed, Hadi Yousuf; Ahmed, Hamdy Abdelfattah; Ahmad, Munir; A. Alavi, Muneeb; Hashim, Muhammad; Abrar, Umair; Adil, Muhammad (Journal of Neonatal Surgery, 2025)
Background: To evaluate the safety and effectiveness of DCB angioplasty in patients with small vessel coronary artery disease. Methods: This prospective observational study included 62 patients with angiographically confirmed SVD who underwent DCB angioplasty between July and December 2023 at Chaudhary pervaiz elahi institute of cardiology Multan. Demographic data, lesion and angiographic characteristics, procedural details, and follow-up outcomes were recorded. ‘For this study, the main endpoint was the 12-month rate of major adverse cardiac events (MACE), comprising cardiac mortality, myocardial infarction, and target lesion revascularization’. Secondary outcomes included binary restenosis, event-free survival, and procedural success. Results: Procedural success was achieved in 96.7% of patients, with only 3.2% requiring bailout stenting. At one-year follow-up, the MACE rate was 8.0%, including 1 cardiac death (1.6%), 2 myocardial infarctions (3.2%), and 2 cases of target lesion revascularization (3.2%). Binary restenosis was detected in 4.8% of patients. Overall, event-free survival was achieved in 91.9% of cases. Conclusion: DCB angioplasty is a safe and effective treatment strategy for small vessel coronary artery disease, offering high procedural success, low restenosis, and favorable one-year clinical outcomes. These findings support the role of DCB as a viable alternative to stenting in appropriately selected patients..